Bactericidal activity of avian complement: a contribution to understand avian-host tropism of Lyme borreliae - Sürth, Valerie (2021)
Complement has been considered as an important factor impacting the host-pathogen association of spirochetes belonging to the Borrelia burgdorferi sensu lato complex, and may play a role in the spirochete's ecology. Birds are known to be important hosts for ticks and in the maintenance of borreliae. Recent field surveys and laboratory transmission studies indicated that certain avian species act as reservoir hosts for different Borrelia species. Nevertheless, our current understanding of the molecular mechanisms determining host tropism of Borrelia is still in its fledgling stage. Concerning the role of complement in avian-host tropism, only a few bird species and Borrelia species have been analysed so far. Here, we performed in vitro serum bactericidal assays with serum samples collected from four bird species including the European robin Erithacus rubecula, the great tit Parus major, the Eurasian blackbird Turdus merula, and the racing pigeon Columba livia, as well as four Borrelia species (B. afzelii, B. garinii, B. valaisiana, and B. burgdorferi sensu stricto). From July to September 2019, juvenile wild birds were caught using mist nets in Portugal. Racing pigeons were sampled in a loft in October 2019. Independent of the bird species analysed, all Borrelia species displayed an intermediate serum-resistant or serum-resistant phenotype except for B. afzelii challenged with serum from blackbirds. This genospecies was efficiently killed by avian complement, suggesting that blackbirds served as dead-end hosts for B. afzelii. In summary, these findings suggest that complement contributes in the avian-spirochete-tick infection cycle and in Borrelia-host tropism.